AB1157 Characteristics of a US Psoriatic Arthritis/Spondyloarthritis Cohort: Baseline Data from the Corrona PSA/SPA Registry. (9th June 2015) - Mease, P.J.; Etzel, C.J.; Kremer, J.M.; Deveikis, S.; Li, Y.; O'Connor, J.; Kavanaugh, A.; Ruderman, E.; Curtis, J.R.; Ritchlin, C.T.; van der Heijde, D.; Solomon, D.; et al.
Abstract : Background: The spondyloarthritides (SpA), such as ankylosing spondylitis (AS) and psoriatic arthritis (PsA) are a group of rheumatologic diseases with shared genetic, pathophysiologic and clinical elements now known to be more prevalent than rheumatoid arthritis (RA). Disease characteristics and outcomes are less well studied than RA. Corrona has investigated over 4000 pts with PsA since 2003. The Corrona SpA registry was launched on 3/21/2013 to include all SpA including AS and other forms of axial and peripheral SpA and more deeply investigate PsA. Enrollment and 6 monthly follow-up data is ongoing. Objectives: The purpose of this analysis is to provide a profile of the demographic and clinical characteristics of the initial patients in this US registry population. The registry will be a rich resource for outcomes research as follow-up time is accrued. Methods: Thus far, 35 of the Corrona investigative sites have been trained to enroll, representing a diverse geographic and private/academic mix. Data at time of enrollment into the registry for a subset of 1411 patients enrolled between 3/21/2013 and 10/17/2014 are presented in this abstract. Data are gathered on demographics, clinical characteristics, referral source, disease activity, function, quality of life, work productivity, comorbid conditions, previous and current treatments, laboratory tests, and imaging. Results: Sixty-nine percent (969/1411) of the patients enrolled in the PsA/SpA registry since 3/13 have a diagnosis of PsA. Median age among all subjects is 53 years. Forty-nine percent of all subjects are female (52% in PsA and 45% in SpA patients) and 51% are obese (BMI >30, as calculated by physician reported height and weight). One-tenth of the subjects have a history of iritis/uveitis, 6% have a history of IBD, but <1% have a history of antecedent infection. A history of fibromayalgia was reported in 9% of patients with PsA and 12% of patients with SpA. Patients with a diagnosis of PsA had a mean CDAI of 11.1 and those with diagnosis of SpA had a mean BASDAI of 3.9. At time of enrollment, 62% were on biologic therapy (majority of these on monotherapy). Eight percent of subjects were on prednisone and 48% were on NSAIDs. Conclusions: The registry has enrolled a growing number of patients with all forms of SpA. Biologic monotherapy use is common among patients with a diagnosis of PsA or SpA. Detailed data on disease characteristics, natural history, treatment and safety outcomes will be presented. Acknowledgements: This study is sponsored by Corrona, LLC. Initial funding for the Corrona SpA registry was provided by AbbVie. In the last two years, AbbVie, Amgen, Astra Zeneca, BMS, Genentech, Horizon Pharma USA, Janssen, Eli Lilly, Novartis, Pfizer, and UCB have supported Corrona LLC. through contracted subscriptions. Disclosure of Interest: P. Mease Grant/research support from: Celgene, Merck, Novartis, Abbvie, Amgen, BiogenIdec, BMS, Genentech, Janssen, Lilly, Pfizer, UCB, Consultant for: Celgene, Merck, Novartis, Abbvie, Amgen, BiogenIdec, BMS, Crescendo, Genentech, Janssen, Lilly, Merck, Pfizer, UCB, Vertex, Speakers bureau: Abbvie, Amgen, BiogenIdec, BMS, Crescendo, Genentech, Janssen, Lilly, Pfizer, UCB, C. Etzel Employee of: Corrona, LLC., J. Kremer Shareholder of: Corrona, LLC., Consultant for: AbbVie, Amgen, BMS, Genentech, Lilly, Pfizer, Employee of: Corrona, LLC., S. Deveikis Employee of: Corrona, LLC., Y. Li: None declared, J. O'Connor Employee of: Corrona, LLC., A. Kavanaugh Grant/research support from: AbbVie, Amgen, Janssen, L.P., UCB, E. Ruderman Consultant for: Corrona, LLC., J. Curtis Grant/research support from: Roche/Genentech, UCB, Janssen, Corrona, Amgen, Pfizer, BMS, Crescendo, Abb Vie, Consultant for: Roche/Genentech, UCB, Janssen, Corrona, Amgen, Pfizer, BMS, Crescendo, Abb Vie, C. Ritchlin Grant/research support from: Amgen, Janssen, and UCB, Consultant for: Abbvie, Amgen, Janssen, Regeneron, and UCB, D. van der Heijde Consultant for: AbbVie, Amgen, AstraZeneca, Augurex, BMS, Celgene, Centocor, Chugai, Covagen, Daiichi, Eli-Lilly, Galapagos, GSK, Janssen, Merk, Novartis, Novo-Norodisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, Shering-Plough, UCB, Vertex, D. Solomon Consultant for: Amgen, Lilly and Corrona, J. Greenberg Shareholder of: Corrona, LLC., Consultant for: AstraZeneca, Celgene, Novartis and Pfizer, Employee of: Corrona, LLC.